2009
DOI: 10.1002/pssc.200881166
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SnS films by low temperature sulfurization

Abstract: Polycrystalline tin sulfide (SnS) films were grown by sulfurization of Sn precursor at low temperatures of 120–220 °C. The p‐ type conductivity SnS film grown at 170 °C comprises densely packed 3–5‐μm‐diameter columnar grains, which is appropriate for use in photoabsorption layers of solar cells. The SnS film had an optical bandgap of about 1.3 eV. Using an appropriate SnS film, n ‐CdS/p ‐SnS heterojunction was fabricated on Mo‐coated soda‐lime glass substrates. These results are the first step toward realizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Orthorhombic SnS is already formed at 195°C together with some metal Sn. Minemura et al [14] also detected the presence of SnS + Sn when Sn evaporated layer on glass was sulfurized at 200°C. The increased sulfurization T at 215°C shows SnS as the predominant phase in conjunction with Sn peaks of lower intensity.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Orthorhombic SnS is already formed at 195°C together with some metal Sn. Minemura et al [14] also detected the presence of SnS + Sn when Sn evaporated layer on glass was sulfurized at 200°C. The increased sulfurization T at 215°C shows SnS as the predominant phase in conjunction with Sn peaks of lower intensity.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, due to the high vapor pressure of SnS, losses of material happen when working at high temperatures. SnS thin films have been deposited by different methods such as thermal evaporation [7][8], co-evaporation [9], spray pyrolysis [10], multilayer-based solid-state reaction [11], RF sputtering [12], sulfurization of Sn sheet [13][14], of Sn evaporated film [14] and of Sn sputtered layer [15][16] between others. The maximum efficiency reported up to date of SnS solar cells is of 4.36% [17].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] On the whole, this report reveals the effective factors hindering the cell efficiency of CdS/SnS-based solar cell. The developed band diagram from the photoemission measurements indicated that both conduction band minimum and VBM at the interface were lower on the CdS side, which is the natural consequence of type-II HJ.…”
Section: Discussionmentioning
confidence: 79%
“…This might be one of the reasons for the low conversion efficiency of the previously reported CdS/SnS related solar cells. [21][22][23] On the whole, this report reveals the effective factors hindering the cell efficiency of CdS/SnS-based solar cell. From the initial stage of finding out the band offset values, it is found that the negative CBO in the type-II HJ will cause interface recombination.…”
Section: Discussionmentioning
confidence: 79%
“…The flow and evaporation rates of the N 2 carrier gas and S source were 800 sccm and 40-50 μmol/min, respectively. The sulfurization equipment have been described elsewhere [2,3,24]. The ntype layers were deposited on the CTS layers for PYS measurements.…”
mentioning
confidence: 99%